Clinical Signs of Temporomandibular Joint Dysfunction in Students of a University in Hanoi - Hong, Dinh Dieu; Tung Kien, Hoang; Thi Minh Huyen, Nguyen; Yen Nhi, Nguyen; Thai Bao, Dinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 1, 2023)
Abstract: Temporomandibular joint dysfunction (TMD) is a common disease, especially increasing in young people, and affects the quality of life. Clinical signs of TMDs are various and complex. Diagnosis of symptoms and prognosis is essential. Therefore, we conducted a cross-sectional descriptive study on 61 patients aged 19-23 who participated voluntarily from February to June 2022 at the Odonto-Stomatology clinic at the University of Medicine and Pharmacy, Vietnam National University. The results showed that the proportion of women with symptoms was higher than that of men. For the clinical symptoms, percentages of the limited range of mandibular movements and mouth gap deviation were quite high (77.0% and 68.9%, respectively). Joint sounds and arthralgia took 31.1% and 24.6%, while myalgia accounted for only 11.5%. In the joint, the pain was detected mainly on the outer surface of the joint (24.6%). In both genders, the masseter muscle was the most painful muscle group. Clinical symptoms are very important in diagnosis, treatment, and prognosis. Keywords: Clinical signs, temporomandibular joint dysfunction, students.